SISI PENGAWASAN PENGELOLAAN DANA DESA - Aprina Nugrahesthy Sulistya Hapsari; Nike Kurniasari; Intiyas Utami (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2018)
The purpose of this research are describe supervision used in managing village funds, identify the role from Badan Permusyawaratan Desa and, explain the monitoring system prevailing on the village funds. This study is conducted in Kaligentong Village and Gladagsari Village in Kabupaten Boyolali. Data collected by interview and its structure to the source of information. The result showed the implementation of supervision is conductucted directly and through the application system of village finance were very helpful in village funds oversees management of transparent and accountable. The supervision conducted by the village administration to carry out monitoring and exercising the functions of planning and monitoring by Badan Permusyawaratan Desa. Beside to supervise, Badan Permusyawaratan Desa can accommodate aspiration of village communities and can be a partner of the village administration. By an improvement of operation and the development of the system of monitoring will influence enhancing accountability and transparency.